2019
DOI: 10.1007/s11695-019-03823-6
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of Problematic and Non-problematic Alcohol Use After Bariatric Surgery

Abstract: Objectives Bariatric surgery is an effective weight loss tool, but an under-communicated side effect may include the increased risk for alcohol problems. Few studies have examined contributors towards alcohol problems following surgery using a qualitative approach. Therefore, the current study aimed to generate insight informed by participants with problematic alcohol use following bariatric surgery, in comparison with participants without. Methods Participants (14; females, n = 9; males, n = 5) completed semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 37 publications
1
37
0
5
Order By: Relevance
“…Most participants were female. One of the studies included two groups of participants: with and without problematic alcohol use [29]. For this review, the decision was made to focus only on results related to participants with PAC (which was possible since the authors distinguished clearly between themes emerging from the discourse of participants with PAC and those without).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Most participants were female. One of the studies included two groups of participants: with and without problematic alcohol use [29]. For this review, the decision was made to focus only on results related to participants with PAC (which was possible since the authors distinguished clearly between themes emerging from the discourse of participants with PAC and those without).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…It involved replacing food with alcohol as a coping strategy. Some participants reported that, before surgery, they had used food to suppress or reduce unpleasant emotions' intensity and, in particular, to manage the distress caused by the psychological problems described earlier (see category 1) [28][29][30][31].…”
Section: Foodmentioning
confidence: 99%
See 2 more Smart Citations
“…Esto puede ser debido a que la privación de alimentos calóricos tras la operación reduce la activación del sistema de reforzamiento del organismo, haciendo que los pacientes necesiten sustituirlos por alcohol y otras sustancias. El uso de alcohol tras la operación también podría ser una forma de afrontamiento de la insatisfacción experimentada tras la operación o la falta de apoyo social percibido (10).…”
Section: Introductionunclassified